Subjective Taste and Smell Changes in Conjunction with Anxiety and Depression Are Associated with Symptoms in Patients with Functional Constipation and Irritable Bowel Syndrome - Jie Liu; Chaolan Lv; Dandan Wu; Ying Wang; Chenyu Sun; Ce Cheng; Yue Yu (Gastroenterology Research and Practice)
Background. Patients with functional constipation (FC) and irritable bowel syndrome (IBS) often report psychological abnormalities and decreased eating enjoyment. Several patients also complain of changes in the sense of smell and taste, but these are often disregarded clinically. Aims. Therefore, there is a need to determine whether taste/smell disturbances and psychological abnormalities are present in patients with FC or IBS and whether these are related to the severity of lower gastrointestinal symptoms. Methods. A total of 337 subjects were recruited, including FC (n=115), IBS (n=126), and healthy controls (n=96). All participants completed questionnaires evaluating taste and smell (taste and smell survey (TSS)), Lower Gastrointestinal Symptoms Rating Scale (LGSRS), Hamilton anxiety scale (HAMA), and Hamilton depression scale (HAMD). TSS recorded information on the nature of taste and smell changes (TSCs) and the impact of these changes on the quality of life. LGSRS was used to assess the severity of lower gastrointestinal symptoms; HAMA and HAMD scales were used to reflect the psychosocial state. This study protocol was registered on the Chinese Clinical Trial Registry (No. ChiCTR-2100044643). Results. Firstly, we found that taste and smell scores were higher in patients with IBS than in healthy controls. Secondly, for FC and IBS patients, LGSRS was significantly correlated with the taste score (Spearman’s rho=0.832, P<0.001). LGSRS was also significantly correlated with HAMA (Spearman’s rho=0.357, P=0.017) and HAMD (Spearman’s rho=0.377, P=0.012). In addition, the taste score was significantly correlated with HAMD (Spearman’s rho=0.479, P=0.001), while the smell score was also significantly correlated with HAMD (Spearman’s rho=0.325, P=0.031). Thirdly, 60.87% and 71.43% of patients complained of taste abnormality, while 65.22% and 71.43% had smell abnormality in the FC and IBS groups, respectively. Meanwhile, 47.83% and 47.62% of patients suffered from anxiety, while 43.48% and 57.14% suffered from depression in the FC and IBS groups, respectively. Finally, we found significant differences in the taste, smell, HAMD, and LGSRS scores between the female and male IBS groups (P<0.050). Conclusions. TSCs and psychological disorders are prominent in FC and IBS patients. Taste abnormalities, as well as anxiety and depression, are significantly correlated with LGSRS. Awareness of this high prevalence of taste/smell abnormalities and the psychological changes among patients with FC and IBS may help better predict and understand the severity of symptoms.